Zotatifin, an eIF4A-Selective Inhibitor, Blocks Tumor Growth in Receptor Tyrosine Kinase Driven Tumors - Gerson-Gurwitz, Adina; Young, Nathan P.; Goel, Vikas K.; Eam, Boreth; Stumpf, Craig R.; Chen, Joan; Fish, Sarah; Barrera, Maria; Sung, Eric; Staunton, Jocelyn; Chiang, Gary G.; Webster, Kevin R.; et al. (Frontiers in Oncology, 2021)
Oncoprotein expression is controlled at the level of mRNA translation and is regulated by the eukaryotic translation initiation factor 4F (eIF4F) complex. eIF4A, a component of eIF4F, catalyzes the unwinding of secondary structure in the 5’-untranslated region (5’-UTR) of mRNA to facilitate ribosome scanning and translation initiation. Zotatifin (eFT226) is a selective eIF4A inhibitor that increases the affinity between eIF4A and specific polypurine sequence motifs and has been reported to inhibit translation of driver oncogenes in models of lymphoma. Here we report the identification of zotatifin binding motifs in the 5’-UTRs of HER2 and FGFR1/2 Receptor Tyrosine Kinases (RTKs). Dysregulation of HER2 or FGFR1/2 in human cancers leads to activation of the PI3K/AKT and RAS/ERK signaling pathways, thus enhancing eIF4A activity and promoting the translation of select oncogenes that are required for tumor cell growth and survival. In solid tumor models driven by alterations in HER2 or FGFR1/2, downregulation of oncoprotein expression by zotatifin induces sustained pathway-dependent anti-tumor activity resulting in potent inhibition of cell proliferation, induction of apoptosis, and significant in vivo tumor growth inhibition or regression. Sensitivity of RTK-driven tumor models to zotatifin correlated with high basal levels of mTOR activity and elevated translational capacity highlighting the unique circuitry generated by the RTK-driven signaling pathway. This dependency identifies the potential for rational combination strategies aimed at vertical inhibition of the PI3K/AKT/eIF4F pathway. Combination of zotatifin with PI3K or AKT inhibitors was beneficial across RTK-driven cancer models by blocking RTK-driven resistance mechanisms demonstrating the clinical potential of these combination strategies.